FAKTOR-FAKTOR PEMICU KONFLIK DALAM RUMAH TANGGA PASANGAN BATAK TOBA KRISTEN DI DESA KARYA INDAH KECAMATAN TAPUNG KABUPATEN KAMPAR - Tetti Sontaria; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted on married couple in Desa Karya Indah Kecamatan Tapung Kampar regency. The purpose of this study is to analyze the conflict in the Batak Toba Christian family in the village of Karya Indah Tapung district Kampar regency. The focus of this study is to analyze the triggers of conflict in the household, conflict resolution efforts and couples pushing factors to maintain households in the Batak Toba Christian Batak couple in the village of Karya Indah Tapung district, Kampar regency. Sampling technique in this study is purposive sampling and set the number of samples of 5 pairs. The author uses qualitative methods and Instruments data is observation, interview and documentation guide. Result of research that factors causing conflict for Toba Christian Batak Tribe, (1) Child (2) Economy (3) Family (4) Environment. The study found there were several attempts to avoid the conflict of the Batak Toba Christian family, namely: family wisdom and customary stakeholder policy.Keyword:Conflict, Household, Family